Graphene : synthesis and applications - Choi, Wonbong, 1963-; Lee, Jo-won, 1952- (Boca Raton : CRC Press, 2012)
'Because of its exceptional electronic and optoelectronic properties, graphene has the potential to become an important material in next-generation electronic and energy applications. This authoritative volume discusses the synthesis, properties, and potential applications of graphene, including in electronic, sensor, energy, and display technologies. Suitable for researchers and graduate students, it provides a cohesive, critical review of graphene nanoscience and technology, offering valuable insight into how this material is made and used'--
'The reported properties and applications of graphene, known as one of the best electronic materials, have opened up new opportunities for future devices and systems, including less-explored industrial applications. This book aims to present an overview of the advancement of research in the area of synthesis, properties and applications, such as electronics, heat dissipation, field emission, sensors, composite and energy. Eleven chapters are presented by experts from each research area'--
Includes bibliographical references and index.
Keywords: Graphene; Graphene -- Industrial applications; SCIENCE / Chemistry / General; SCIENCE / Solid State Physics; TECHNOLOGY & ENGINEERING / Material Science